Helicobacter pylori heterogeneity in patients with gastritis and peptic ulcer disease - Armitano, Rita Ines (2013)
Genetic diversification allows Helicobacter pylori to persist during chronic colonization/infection. We investigated the intra-host variation of several markers that suggested microevolution in patients with chonic gastritis (CG) and peptic ulcer disease (PUD). One-hundred twenty-six isolates recovered from 14 patients with CG and 13 patients with PUD were analysed. cag pathogenicity island (cagPAI), oipA, vacA, bab gene status and the presence of jhp0926, jhp0945, jhp0947, jhp0949 and jhp0940 genes from the genomic Plasticity Zone (PZ) were taken into accout to investigate intra-host variation. lspA-glmMRFLP was performed to identify mixed infections. Only one patient was colonised/infected by two ancestrally unrelated strains. Among the 126 isolates, a significant association among cagPAI genotypes, oipA status and vacA alleles was indicated. Complete cagPAI, oipA ??on??, and vacA s1-m1 variants were significantly found in patients with PUD, without intra-host variations. Isolates from 7/14 patients with CG lacked babA in all chromosomal loci. In contrast, isolates from all or several biopsies of PUD patients carried babA, but in one patient only, the isolates showed positive Lewis b (Leb) binding assay. Considering cagPAI, vacA, oipA, bab genotypes, intra-host variation was also significantly higher in patients with CG. Conversely, a similarly high intra-host variation in almost PZ genes was observed in isolates from patients with CG and PUD. In conclusion, the lowest intra-host variation in cagPAI, oipA, vacA, and bab genes found in patients with PUD suggests the selection of a particular variant along the bacteria-host environment interplay during ulceration development. However, the predominance of this variant may be a refletion of the multifactorial etiology of the disease rather than the cause, as it was also found in patients with CG. The intra-host variation in PZ genes may predict that this genomic region and the other markers of microevolution studied evolve under diverse pressure(s).